Influence of spraying perhydropolysilazane coating on friction and wear of end-face metal during the mixing process. (November 2022) - Han, Deshang; Wang, Yu; Pan, Yi; Qiu, Jian; Wang, Jing; Wang, Chuansheng; Liu, Haichao
Abstract: Perhydropolysilazane (PHPS) is an inorganic polymer composed of -(SiH2 –NH)- repeating structural units. When used as a coating material, it has the advantages of good solubility, simple curing conditions, flexible curing process, and simple preparation method and can significantly save processing time and cost. This paper investigates the frictional behavior of the PHPS-coated metals cured at different temperatures with NR/BR/SBR composites. The effects of different curing temperatures on the PHPS coatings are characterized using infrared absorption spectroscopy. After curing, the asymmetric stretching and oscillating vibration peaks of the Si–O–Si groups are formed, which is attributed to the hydrolysis reaction of Si–N and Si–H and the subsequent cross-linking curing reaction. The denseness of PHPS coatings increases with the increase in curing temperature. When the curing temperature is 400 °C, the cross-linking curing effect of PHPS is the strongest, and the denseness of the PHPS coating is the best. Furtherly, the frictional wear of metal with NR/BR/SBR composites is analyzed from the perspective of the formulation process for the first time, and the ratio of abrasive wear and corrosion wear is calculated qualitatively. It is found that increasing the curing temperature of the PHPS coating can significantly reduce metal wear and improve corrosion resistance, which is attributed to the formation of the ethanol-water molecular film on the surface of the PHPS coating. The ethanol-water molecular film isolates the contact between the PHPS-coated metal and the NR/BR/SBR composite to a certain extent, acting as a lubricant and thus reducing friction. After rubbing the cured PHPS-coated metal with NR/BR/SBR composite, the wear amounts of the cured PHPS-coated metal at 200 °C, 300 °C, and 400 °C are reduced by 49.06%, 66.74%, and 87.33%, respectively, and the corrosion resistance are improved by 51.52%, 63.64%, and 78.79%, respectively. Highlights: The friction behaviour of silicone-coated metal and rubber composites cured at different temperatures was investigated. The metal wear of the coating cured at 300℃ is reduced by 66.74%, and the corrosion resistance is increased by 63.64%. After curing at 400℃, the metal wear is reduced by 87.33%, and the corrosion resistance is increased by 78.79%.